Synthesis, Molecular Characterization and Preliminary Antioxidant Activity Evaluation of Quercetin Fatty Esters. (6th September 2013) - Mainini, Francesca; Contini, Alessandro; Nava, Donatella; Corsetto, Paola Antonia; Rizzo, Angela Maria; Agradi, Elisabetta; Pini, Elena
Abstract: Quercetin shows interesting pharmacological effects, but its use in topical applications is limited by its low skin permeability and solubility. In this work, the synthesis of highly lipophilic quercetin esters with oleic, linoleic and linolenic acid useful as topical quercetin prodrugs is reported. Partial OH esterification is advisable to maintain the antioxidant activity of these compounds; tetraesters and triesters can be achieved by modulating the reaction conditions utilized for the total esterification of quercetin. The chemical structures of the esters were proven by spectroscopic techniques; quantum chemical NMR calculation were mandatory to unequivocally assign the free position in triesters. Finally, the antioxidant activity of all the synthesized compounds was determined by the 2, 2‐diphenyl‐1‐picryl‐hydrazyl method and by 2, 2‐azinobis(3‐ethyl‐benzothiazoline‐6‐sulfonic acid) assay.